Letrozole as premedication of high intensity focused ultrasound treatment of uterine fibroids: A retrospective observation study - Chen, Wei-Chun; Hsu, Chia-Chen; Huang, Huei-Jean; Cheng, Wei-Jen; Chang, Ting-Chang; Chou, Hung-Hsueh (Frontiers in Medicine, 2022)
Background: No reports on Letrozole as a pretreatment before ablation of uterine fibroid with high intensity focused ultrasound (HIFU), so a retrospective observation study was performed to evaluate the response of different pre-HIFU medication. Methods: We collected patients with single uterine fibroid receiving HIFU ablation from January 2018 to April 2021. All enrolled patients were classified into three group: group A (no pre-HIFU medication use), group B (Pre-HIFU letrozole use), group C (pre-HIFU gonadotrophin releasing hormone analogue, GnRHa). Further associated clinical data and treatment response after HIFU treatment were reviewed and evaluated. Results: A total of 39 patients including 21, 7, and 11 in group A, B, and C were collected respectively. After pre-HIFU medication, no difference of fibroid volume was found (A: 251.4, B: 360.6, C: 409.4 cm3, p=0.250), and GnRHa group had significantly larger volume reduction than Letrozole users (38.6% vs. 16.4%, p=0.007). The incidence of hypoestrogenic symptoms was higher in GnRHa group than in letrozole users (27.3% vs. 0, p=0.170). GnRHa group had more sonication time (p=0.001), treatment duration (p=0.002), and ablated energy (p=0.001) than group A and B. The treatment efficiency was higher in letrozole group than that in other 2 groups (4.52 vs. 2.39 vs. 2.34 cm3/min, p=0.050). For patients with fibroid over 10cm in diameter, letrozole group had even better energy efficiency (p=0.067), treatment speed (p=0.007), treatment efficiency (p=0.001), NPV per energy (p=0.005), and NPV per sonication (p=0.004) than other 2 groups. Counclusion: Letrozole as a pretreatment medication before HIFU treatment might increase the energy efficiency and treatment efficiency of its ablation of uterine leiomyoma, especially for fibroid over 10cm. Future study of larger patient number is needed to confirm our results.